GROWTH PERFORMANCE AND CARCASS YIELD OF HELMETED GUINEA FOWL (NUMIDA MELEAGRIS) MALE KEETS RAISED IN DIFFERENT HOUSING SYSTEMS OF A TROPICAL ENVIRONMENT - Idowu, Olubukola P. A.; Adeyeye, Emmanuel A.; Amos, Adedoyin T.; Kareem, Damilola U.; Bamgbose, Adeyemi M.; Idowu, Olusegun M. O.; Sogunle, Olajide M. (FUDMA Journal of Sciences, 2025)
This study evaluated the growth performance and carcass yield of male helmeted guinea fowl (Numida meleagris) keets raised under three housing systems: deep litter, battery cage, and deep litter, which run in a tropical environment. The objective was to assess the influence of housing on bird productivity and carcass characteristics to inform best practices for sustainable guinea fowl production. Two hundred sixteen eight-week-old male keets were randomly distributed across the housing systems in a Completely Randomized Design, with feed and water provided ad libitum for 16 weeks. Growth performance was measured weekly, while carcass and gastrointestinal traits were evaluated post-slaughter. Data were analyzed using Analysis of Variance (ANOVA), and significant means were separated using Duncan’s Multiple Range Test at a 5% significance level. Results showed significant differences (p < 0.05) in feed intake and some carcass parameters among housing systems. Deep litter with run birds exhibited a superior dressing percentage (74.25%) and higher ether extract content in thigh meat (5.02%). In contrast, battery cage birds showed higher drumstick meat percentage and crude protein levels. The housing system significantly influenced oesophagus length and selected gastrointestinal segments. It is concluded that deep litter with run offers a favourable environment for improved carcass traits and may enhance nutrient deposition in meat, suggesting it is a viable system in tropical settings. These findings contribute to the knowledge of guinea fowl production and recommend further investigation into the interactive effects of housing and environmental variables on performance outcomes.